Real earnings management in family firms: the effect of group affiliation, leverage and diversification - Wan Nadiah W Abdul Rahman
Earnings management can be categorised into Accrual Earnings Management (AEM) and Real Earnings Management (REM). Unlike the former method, the latter has a direct effect on firm's cash flows. REM is also preferred to AEM since it is more difficult to detect, yet relatively easier to implement than AEM. Family group affiliation, leverage and diversification have been used by controlling shareholders to smooth expropriation activities and exacerbate REM. However, to date, none of the empirical research has examined the relationships of the three variables with REM simultaneously. Despite the high rate of earnings management in Malaysia, studies f REM are still limited. In Malaysia, family group affiliation dominates half of its capital market and these firms usually would establish business affiliation with complex pyramidal structure. The resulting structure is likely to increase agency problems, entrenchment and tunnelling activities associated with REM. Accordingly, the objective of this research is to examine the effects of these three variables on REM, and the moderating role of diversification on the relationship between leverage and REM. Secondary data was obtained from Thomson Reuters Eikon Datastream and firm's annual report. Stata software was used in the data analysis. The final sample consists of 117 non-financial family business group affiliation firms listed on Bursa Malaysia in the period 2006 to 2015. Balanced panel data using specification methods of Fixed Effect (FE) and Random Effect (RE) were conducted to test the hypotheses. The relationship between family group affiliation, leverage, diversification and AEM was also tested as additional analysis. The findings reveal a negative and significant relationship between the size of family group affiliation and REM measured by abnormal production cost (AB_PROD), abnormal discretionary expenses (AB_DIS) and the aggregate of AB_PROD and AB_DIS (REM_2). However, the complexity structure of family business groups failed to provide any significant relationship with any REM proxies. Meanwhile, short-term debt (STD) shown positive and significant relationship with all REM proxies except AB_PROD and REM_2. On the other hand, the relationship between long-term debt (LTD) and REM in form of AB_DIS and the aggregate of REM (REM_ALL) are negatively significant. In addition, the result between product diversification (PRO_HER) and REM is mixed and insignificantly correlated, while geographic diversification (GEO_HER) revealed negatively significant relationship with AB_PROD and REM_2. The findings also suggest that corporate diversification partially moderates the relationship between leverage (STD and LTD) and REM. The results of the study provide evidence of increasing and decreasing REM by family business group firms to manipulate earnings. The study partially supports the proposed hypotheses and offer new variables which contribute to the practice of REM in Malaysia. Investors, auditors, analysts and practitioners should consider family business group affiliation firms as a factor for increasing and decreasing earnings manipulation behaviour. The results also provide new input for regulators and standard setters to consider minor reform in prevention and controlling strategies for the sake of protecting stakeholders.